Methodological Advances in Research on Emotion and Education - Zembylas, Michalinos; Schutz, Paul A. (Springer International Publishing : Imprint: Springer, 2016)
This volume presents different conceptual and theoretical frameworks as well as research methods that have helped educational researchers to study emotions. It includes innovative approaches that push the methodological boundaries that have served educational researchers until now and proposes new ways of researching emotions in educational contexts. In particular, this edited volume provides a historical frame for studying emotions. It connects theoretical/epistemological views with choice of research methods and describes specific methods helpful in doing research on emotions as they are grounded in different theoretical and disciplinary traditions such as psychology, philosophy, sociology, history, political science, cultural studies, and feminist studies. Finally, it appreciates the contextual and international dimensions of studying emotions in education and contributes to ongoing debates about the implications of our methodological choices for understanding emotion in education. This combination of variety, timeliness, potential for transformation of the field, and uniqueness make this a very valuable resource to introduce new scholars in the field alongside established scholars.